Respuestas de anticuerpos pasivos y efecto de la edad de los lechones en la vacunación contra el virus de la peste porcina clásica - Carranza, Alicia; Ambrogi, Arnaldo; Pelliza, Bibiana; Romanini, Silvia (Revista Colombiana de Ciencias Pecuarias, 2016)
Summary The vaccination with the Chinese strain is used to prevent the Classical Swine Fever. But the presence of passive antibodies and age of piglets at the time of vaccination can originate an unsatisfactory active humoral response. In this study 7, 21 and 56 days animals with and without passive immunity, were vaccinated. Blood samples were taken at the time of vaccination and then at 15 and 45 days later. The animals responded in different ways to vaccination, according to the presence or not of passive antibodies. It was observed that as greater the age of vaccination, greater was the percentage of animals that responded to the vaccine in the last sampling. The ELISA technique did not allow detecting antibodies 15 days after vaccination.